A Transforming Path – The Pilgrims' Songs. Issue 2 (1st September 2021) - Butting, Klara
Abstract: This article introduces the composition of the Pilgrim Psalms (120–134). Psalm 122 plays a key role in this. Jerusalem, the destination of the trip, will be a stop on the way. The pilgrimage to the place of faith becomes a path to the points of suffering in society. The background comes into view with Psalm 123, a psalm lacking an expression of trust, the low point of the entire trip. It begins the spiritual work that always occurs in places of faith: The language of power and the language of religion have become intermingled and perverted perceptions of God. Psalm 123 counteracts this misunderstanding of God by addressing God. In Psalm 123 the power and nature of prayer can be experienced intensely. Prayer is the discovery of God's surrender to us humans and an act of freedom in relation to the existing balance of power.